Circular Economy Recent Advances, New Perspectives and Applications - Zhang, Tao (IntechOpen, 2021)
Nowadays, the restriction of resources and the environment is very severe. A circular economy is the only way to sustainable development, but how this works still needs more exploration. The series of studies carried out by the author are described in detail in this book.